Impact of Organizational Culture on Job Satisfaction - Sadikin, Mochamad Rizki; Junaedi, Junaedi; Desnatria, Desnatria (International Journal of Entrepreneurship and Business Management, 2024)
The purpose of this study was to determine the impact of organizational culture, work environment, and compensation on job satisfaction. The sample in this study were 40 employees, with the data analysis technique used was sequential equation modelling. The study results explain that the influence of organizational culture has a positive and significant impact on employee performance. Work Motivation has a positive and significant impact on employee performance. job satisfaction has a positive and significant impact on employee performance. Organization climate, work motivation and job satisfaction have a positive and significant impact on job satisfaction